Appennines settlement evolution and transformation analysis with GIS instrument - Alessia Gualtieri; Bernardino Romano (European Regional Science Association (ERSA), 2005)
The analysis of the spatial and structural changes of the urban web represents a valid key of reading not only for the study of the landscape evolution of a datum territory but also for the understanding of the social and economic tendencies that will influence the choices in phase of planning and the following managerial politics. The proposed job illustrates some methodologies, supported from GIS technique, for the analysis of the modifications intervened so far in use and landscape picture, formulating the structure of some evolution entity indexes connected to past and current planning, both to the consequent spontaneous phenomenons to the economic logics. The result is that to compare the found trends of arrangement in the demografic-social-productive sphere with the changes in progress aspects loaded instead with environmental system through the analysis of the actual settlement structure and urbanistic instrument.
Keywords: 330